Environmental measurement study of double-aging neighborhoods under the EPA-S model in China - Mingyu, Chen; Cao, Gan; Lanchun, Bian (Frontiers in Environmental Health, 2024)
The “double aging” problem of the aging population and the simultaneous aging of the community's physical environment will become a huge challenge in highly urbanized areas of the world, and China's performance is becoming more and more obvious, affecting the physical and mental health and quality of life of the elderly. Nowadays, the paradigm of solving the double aging problem with the concept of “active aging” is gaining international acceptance, which means the elderly are centered on the design and construction of a community environment that maintains their ability to live independently and promotes active social interaction in urban regeneration. However, existing research still has shortcomings in how to apply the perspective of active aging to establish an indicator system for evaluating the built environment of “double aging” neighborhoods and formulate action strategies. The study constructs a theoretical analysis framework of EPA-S (E-Environment supports, P-Personal abilities, A-Activity behaviors, S-State of healthy and active life) from the perspective of active aging and builds the model based on that. This observational study designed the survey content and collected sample data in four typical double-aging neighborhoods in Beijing for multi-layer linear regression analysis to verify the reliability of the model and the correlation between indicators. It found that the design of the “EPA-S” model has a certain degree of credibility. In addition to personal socioeconomic factors, active living abilities, and material environmental support also have a significant impact on the mental health and happiness of the elderly. Specifically, being more involved in community public affairs and collective cultural and recreational activities, and better improving the quality of public activity venues and service facilities within walking distance of the elderly are related to the elderly maintaining good physical and mental health. The “EPA-S” model established in this study can be used as a reference tool to evaluate the active aging level of “double-aging” neighborhoods. At the same time, the analysis results of each variable also provide important inspiration for formulating specific neighborhoods' regeneration strategies.